2015
DOI: 10.20286/jech-02036
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Health Literacy with Health Status, Preventive Behaviors and Health Services Utilization in Baluchistan, Iran

Abstract: Background and Objectives: Health Literacy has been defined as the cognitive and social skills that determine the motivation and ability of individuals to gain access to, understand and use information in ways which promote and maintain good health. People with inadequate health literacy have poorer health status. Thus, the aim of this study was to determine the status of health literacy and its relationship with general health status, use of health services and preventive behaviors. Materials and Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 19 publications
5
46
2
1
Order By: Relevance
“…Overall health literacy score was determined by aggregating correct answers from all questions and Research article ranged between 0 and 20. Scores were then categorized into 3 groups: inadequate (< 10), moderate (10)(11)(12)(13)(14) and adequate (> 14). Independent variables included age, sex, education, residence and occupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall health literacy score was determined by aggregating correct answers from all questions and Research article ranged between 0 and 20. Scores were then categorized into 3 groups: inadequate (< 10), moderate (10)(11)(12)(13)(14) and adequate (> 14). Independent variables included age, sex, education, residence and occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of health literacy are often observed in developing settings such as the Middle Eastern context (12). In the Islamic Republic of Iran, one of the most populated countries in the Middle East, several studies have tried to measure health literacy and reported overall insufficient health literacy levels, ranging from 41% in adults in the central province of Yazd to 68% in the southeastern province of Baluchistan (13). Previous studies have also indicated varying levels of health literacy among different subpopulations of patients, e.g., 70% insufficient health literacy in patients with diabetes (14); and age groups, e.g., 79.6% insufficient health literacy among older adults (15).…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy consists of cognitive and social skills determining people's motivation and capacity to obtain, understand, and use health information to inform appropriate health care decisions and behaviors (1). Health literacy can be considered a capacity that empowers people to make decisions related to their health (2,3).…”
Section: Contextmentioning
confidence: 99%
“…HL are better at self-care skills [3][4][5]. Indeed, inadequate HL is a serious obstacle to self-care behaviors in patients with chronic diseases and can affect the participation of patients in self-care [3].…”
mentioning
confidence: 99%
“…Indeed, inadequate HL is a serious obstacle to self-care behaviors in patients with chronic diseases and can affect the participation of patients in self-care [3]. Also, the prevalence of chronic diseases is higher in people with inadequate HL [4]. Studies have shown that among the levels of HL, communication and critical HL skills are the essential and necessary factors for improving self-care in patients with chronic diseases because these skills increase self-esteem patients improve their ability to communicate effectively with health care providers and patients' capabilities to participate and work with the health system [3].…”
mentioning
confidence: 99%